High-Throughput Screening of Senescence Markers in Hematopoietic Stem Cells Derived from Induced Pluripotent Stem Cells - Jose, Shyam Sushama; Bendickova, Kamila; Fric, Jan (Methods in molecular biology (Clifton, N.J.), 2018)
The successful development and characterization of human induced pluripotent stem cells (iPSCs) provides a powerful tool to study the molecular mechanisms that control cell fate decisions and differentiation toward distinct lineages. Here we focus on the ability of donors derived iPSCs to differentiate toward hematopoietic progenitor cells and on the analysis of their telomere length. The ability to screen telomere length in individual donors is important for defining cellular senescence, which correlates with their differentiation potential toward hematopoietic lineages. We have modified iPSC culture protocol and telomere length analysis to suit for high throughput screening of telomere length in large number of individual donors. This approach can be used to demonstrate the heterogeneity or changes of telomere length and its shortening as an exclusion criterion for selection of suitable donors for future stem cell therapies.
Keywords: Humans; stárnutí buněk; Cellular senescence; Hematopoiesis; rychlé screeningové testy; Induced Pluripotent Stem Cells; hematopoetické kmenové buňky; lidé; Biomarkers; Telomere length; Tissue Array Analysis; indukované pluripotentní kmenové buňky; biologické markery; čipová analýza tkání; Hematopoietic stem cells; Induced pluripotent stem cells; Hematopoietic Stem Cells; Cellular Senescence; Cell Culture Techniques; High-Throughput Screening Assays; buněčné kultury